The Last Stargazers : The Enduring Story of Astronomy's Vanishing Explorers - Levesque, Emily (Naperville, Illinois : Sourcebooks, 2020)
This book "combines the exciting travels of ... astronomer Emily Levesque with the misunderstood antics of a scrappy (and shrinking) crew of scientists working with stars and telescopes. She dissects both the romance and the real human curiosity that is so important to our exploration of space. Amidst the lonely quiet of stargazing to wild bears loose in the observatory, these love stories of astronomy show how scientists are going beyond the machines to infuse important creativity and intimate passion into the stars, inspiring future generations to peer skyward in pursuit of the universe's secrets"--
First light -- Prime focus -- Has anybody seen the condors? -- Hours lost : six. Reason : volcano -- The harm from the bullets was extraordinarily small -- A mountain of one's own -- Hayrides and hurricanes -- Flying with the stratonauts -- Three seconds in Argentina -- Test mass -- Target of opportunity -- The supernova in your inbox -- Synoptic future.
Includes bibliographical references and index.
Keywords: Levesque, Emily; Astronomy -- Popular works; Astronomers -- Popular works; Astronomical observatories -- Popular works